Public survey data of the research study “Ready for change? Sustainable management of common natural resources”: survey data from 2020 and 2021 - University of Latvia, Advanced Social and Political Research Institute (ASPRI) of the Faculty of Social Sciences (My University, 2023)
Public survey data of the research study “Ready for change? Sustainable management of common natural resources”: survey data from 2020 and 2021 The data set (see the description of the data set below) and its accompanying information include public survey data collected in November 2020 and 2021 as part of the Fundamental and Applied Research project "Ready for change? “Sustainable management of common natural resources” (lzp-2019/1-0319). Data collection took place from November 9, 2020, to November 30, 2020, and from November 1, 2021, to November 29, 2021. Ongoing environmental collapse is putting increasing pressure on ecosystems and social communities, particularly, in the regions of Latvia. Thus, representative survey of Latvia human population has been conducted to assess the societal response to environmental collapse in the context of the social and economic reality in the regions of Latvia. The survey achieved a sample size of 1015 respondents - residents of the Republic of Latvia aged 18 and older. The anonymized data set was obtained through a random digit dialing (RDD) method, involving the generation of random combinations of telephone numbers, and conducted through computer-assisted telephone interviews (CATI). The survey was conducted by the research center Latvijas Fakti, commissioned by researchers from the University of Latvia within the framework of the Fundamental and Applied Research project "Ready for change? “Sustainable management of common natural resources” (lzp-2019/1-0319), conducted at the Advanced Social and Political Research Institute (ASPRI) of the Faculty of Social Sciences of the University of Latvia (LU). The research was funded by the Latvian Council of Science.

Description of the data sets: 1. Combined Survey Data File for 2020 and 2021 (File Name: RfC_Dati_20202021.csv, also available in .sav format). Includes weight coefficients for individual years. Total of 2035 cases or respondents. 2. 2020 Survey Data File. (File Name: RfC_Dati_2020.csv, also available in .sav format). Consists of 1020 cases or respondents. 3. 2021 Survey Data File. (File Name: RfC_Dati_2021.csv, also available in .sav format). Contains 1015 cases or respondents. Note: The datasets in points 2 and 3 have the same number of variables (76 variables) as the combined data file mentioned in point 1. The combined data file in point 1 has 2035 cases, which is the sum of the 2020 data file (1020 cases) in point 2 and the 2021 data file (1015 cases) in point 3. 4. Variable and Value Labels for Data Sets 1-3. (File Name: RfC_MainigoInfo_20202021.xlsx) The datasets include 76 variables, of which: 1. 67 variables are related to survey questionnaire questions and responses, including combinations of socio-demographic variables. (Survey questionnaire in the document: RfC_Aptaujas_anketa.docx); 2. 5 variables pertain to additional information about regions. (Details can be found in the file: RfC_20202021_Apdzivotu_vietu_mainigo_metodologija.txt); 3. 2 variables are associated with weights and their methodology for particular years. For the 2020 survey (file: RfC_Svari2020.xlsx) and for the 2021 survey (file: RfC_Svari2021.xlsx). 4. Additionally, there are the ID variable (ID) and the research year identifier (gads).
Keywords: environmental attitude; economic-ecologic process; environmental behaviour; pro-environmental behaviour; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Sociology